Detection of fraud in canned tuna - Rodrigues, M. V.; Ferri, Y. G.; Ceron, T. F.; Sgarbosa, S. H. P. V. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Canned tuna is defined as a product made with tuna, packaged in hermetic way, followed by sterilization to avoid contamination and multiplication by microorganisms, beyond to propitiate integrity until the end of shelf life of the product. For this product processing, Ministério da Agricultura, Pecuária e Abastecimento (MAPA) published the Normative Instruction 46 of December 15th of 2011, which regulates the production of canned tuna in Brazil (BRASIL, 2011). Thus, fraud occurs for substitution of fish species not allowed by legislation. This study aimed standardize the detection of fraud in tuna canned by polymerase chain reaction (PCR) and real time PCR (qPCR).